Drop spreading and penetration into pre-wetted powders - Marston, J; Sprittles, J; Zhu, Y; Li, E; Vakarelski, I; Thoroddsen, S (2013)
We present results from an experimental study of the impact of liquid drops onto powder beds which are pre-wetted with the impacting liquid. Using high-speed video imaging, we study both the dynamics of the initial spreading regime and drainage times once the drop has reached its maximum spread on the surface. During the initial spreading stage, we compare our experimental data to a previously developed model which incorporates imbibition into the spreading dynamics and observe reasonable agreement. We find that the maximum spread is a strong function of the moisture content in the powder bed and that the total time from impact to complete drainage is always shorter than that for dry powder. Our results indicate that there is an optimum moisture content (or saturation) which leads to the fastest penetration. We use simple scaling arguments which also identify an optimum moisture content for fastest penetration, which agrees very well with the experimental result.